Urban requalification and criminal dynamics: case study of the Centro Vivo program in Belo Horizonte, Minas Gerais, Brazil - Hausemer, Bruna; Salgado, Nayara de Amorim; Silva, Braulio Figueiredo Alves da (FCL-UNESP Laboratório Editorial, 2021)
This article studies the transformation process of the central region of Belo Horizonte-MG focusing on the main sociological theories which interpret the criminal phenomenon through its environmental components, examining the evolution of criminality in this space based on the analysis of the criminal dynamics of robberies in the so-called “Hipercentro” between 1998 and 2015, encompassing a historical series of data which comprises a period before, during and after the realization of the largest and most recent program of the municipal government for urban requalification directed to the region: Centro Vivo. The notes generated show that the hotspots of robberies are not evenly distributed throughout downtown, but concentrated in certain regions, and that, after the urban interventions of Centro Vivo, those hotspots suffered attenuation, without dispersion or migration of criminality.